(untitled) (Estudios de Historia de España, 2017)
The reign of Catholics Kings, especially for his first years, supposes a interesting historical context from the point of view of the utilization of varied forms of propaganda and exaltation of the royal power. This article offers a systematical synthesis of this forms and of his political and cultural meaning.